LEADERSHIP IN THE FACE OF POST-PANDEMIC CHANGES - Pozzo Arbigaus, Lindamir (Revista Gênero e Interdisciplinaridade, 2023)
Being a leader within an organization has always been a challenge. Faced with the evolution of globalization and organizational and technological disruptions, this challenge remains. The literature addresses the main processes of transformation that have been taking place and the needs for change imposed on leaders, who seek beyond personal performance, also organizational performance. The objective of this work is to approach the main styles of leadership, how leadership can affect the performance of a company. The methodology proposed in the present study was of a qualitative and descriptive nature, with research and bibliographical surveys in books and websites of scientific relevance.